Peran Dewan Pengawas Syariah Terhadap Shariah Compliance di PT. Bank Pembiayaan Rakyat Syariah (BPRS) Bangka Belitung - Hermanto, Hermanto (EJESH: Journal of Islamic Economics and Social, 2023)
Sharia Financial Institutions are financial institutions whose operations are based on sharia principles. The existence of a sharia economic fatwa issued by DSN-MUI is a guideline for LKS in running products so that they comply with sharia contracts. To maintain the implementation of sharia principles in LKS, there is a Sharia Supervisory Board as a representative of DSN-MUI whose position is to act as a sharia compliance supervisor whose task is to maintain conformity between DSN-MUI fatwas and practices in LKS. The study in this paper aims to analyze the role of DPS in PT. BPRS Bangka Belitung regarding the implementation of Shariah Compliance then tried to formulate a strategy to optimize this role. among others: DPS in charge is human resources who must have special competence not only in the field of Islamic law but also in the banking sector, structured training for DPS to understand the object of supervision comprehensively, DPS independence in organizational structure is an important issue so that DPS avoids conflict of interest, the intensity of supervision must comply with the rules, DPS must be involved in every contract transaction that occurs so that DPS can carry out supervision at all times. The DPS profession is a profession that is not carried out on a part-time basis. One of the innovations to increase the optimization of the supervisory role, apart from normative solutions, this research also provides a concrete solution in the form of a digital supervision innovation called "LAKUVADEH" (Integrated Validation Accountability and Coordination Service by the Sharia Supervisory Board). This innovation was analyzed using the Deming PDCA Cycle (Plan, Do, Check, Action) method